Feasibility of dominant intraprostatic lesion boosting using advanced photon-, proton- or brachytherapy. Issue 3 (December 2015) - Andrzejewski, Piotr; Kuess, Peter; Knäusl, Barbara; Pinker, Katja; Georg, Petra; Knoth, Johannes; Berger, Daniel; Kirisits, Christian; Goldner, Gregor; Helbich, Thomas; Pötter, Richard; Georg, Dietmar
Abstract: Background and purpose: Advancements in imaging and dose delivery enable boosting of the dominant intraprostatic lesions (DIL), while maintaining organs-at-risk (OAR) tolerances. This study aimed to assess the feasibility of DIL boosting for volumetric modulated arc therapy (VMAT), intensity modulated proton therapy (IMPT) and high dose rate brachytherapy (HDR-BT). Material and methods: DILs were defined on multiparametric magnetic resonance imaging and fused with planning CT for twelve patients. VMAT, IMPT and HDR-BT plans were created for each patient with an EQD2 α / β DIL aimed at 111.6 Gy, PTVinitial D pres was 80.9 Gy (EBRT) with CTV D 90%  = 81.9 Gy (HDR-BT). Hard dose constraints were applied for OARs. Results: Higher boost doses were achieved with IMPT compared to VMAT, keeping major OAR doses at similar levels. Patient averaged EQD2 α / β D 50% to DIL were 110.7, 114.2 and 150.1 Gy(IsoE) for VMAT, IMPT and HDR-BT, respectively. Respective rectal wall D mean were 30.5 ± 5.0, 16.7 ± 3.6, 9.5 ± 2.5 Gy(IsoE) and bladder wall D mean were 21.0 ± 5.5, 15.6 ± 4.3 and 6.3 ± 2.2 Gy(IsoE). Conclusions: DIL boosting was found to be feasible with all investigated techniques. Although OAR doses were higher than for standard treatment approach, the risk levels were reasonably low. HDR-BT was superior to VMAT and IMPT, both in terms of OAR sparing and DIL boosting.